IN VITRO ANTIMICROBIAL ACTIVITY OF THE LEAF EXTRACTS OF ARGEMONE MEXICANA AGAINST SELECTED PATHOGENIC MICROORGANISMS - C. KRISHNA KUMARI; C. SHANMUGA REDDY; Y. RAJA RATNA REDDY; D. NARAPA REDDY; C. DAMODAR REDDY (International Journal of Pharma and Bio Sciences, 2013)
This article describes the antimicrobial properties of Argemone mexicana a plant that grows in tropical and subtropical regions. The antimicrobial efficacy of different solvent extracts (Ethyl acetate, methanol and aqueous) of Argemone mexicana leaves against different pathogenic microorganisms was investigated using the disc diffusion method. The aqueous and methanolic extracts exhibited potent antibacterial activity against two Gram positive (Enterococcus fecalis, Staphylococcus aureus) and two Gram negative (Klebsiella pneumoniae, Proteus mirabilis) bacteria and moderate antifungal activity against Aspergillus fumigatus and, Cryptococcus neoformans. The zone of inhibition was found to be in the range of 10.0 - 25.0 mm when tested at a concentration range of 75 - 500 μg/disc. Differences in the antimicrobial activity can be attributed to the presence of different phytochemicals present in these extracts. Phytochemical analysis of different fractions that have shown efficacy may contribute to the development of new antimicrobial agents.